Stress-testing Book History Models as a Framework for Studying Translations in Society: Censorship and Patronage in Occupied Japan. (October 2019) - Wakabayashi, Judy
Abstract : Book history models are stress-tested here by examining the agents and influences affecting translated books in the extreme circumstances represented by the American-led Occupation of Japan. Here an externally imposed system of simultaneous censorship and support dominated Japanese translations, both with the goal of reorienting postwar Japan towards democracy. Book history models are reevaluated in terms of their heuristic adequacy for translation history. The article highlights factors relevant to this situation of foreign occupation (including events removed in time and place) and the role of agents not specifically accounted for in existing models. Focusing on this narrow timeframe and the dual policies of censorship and patronage in the relatively hermetic book world of occupied Japan suggests how book history models might better accommodate not only situations of occupation elsewhere but also less extreme situations.